TEKNIK ASSESMEN OBSERVASI DAN PERCAKAPAN SEBAGAI UPAYA PEMANTAUAN PERKEMBANGAN BAHASA ANAK DI TK PAMARDI SIWI NANGGULAN MAGUWOHARJO SLEMAN YOGYAKARTA - Muhammad Habibu Rahman (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
This paper presents the importance of each educator to monitor children's language development. Language development in early childhood is very unique and interesting. To monitor language development in early childhood, every educator needs to conduct an assessment of learning activities and play activities in school. This study aims to determine the assessment techniques with observation and conversation in an effort to monitor the language development of children in Pamardi Siwi Kindergarten Nanggulan Maguwoharjo Sleman Yogyakarta. Data sources in this study include the principal, and the class teacher. Data collection is done by observation, interviews, and documentation. Data analysis is done by data reduction, data presentation, and conclusion drawing. Based on the results of the study it can be concluded that the assessment used at the Pamardi Siwi Kindergarten is in accordance with the Minister of Education and Culture Regulation 137 of 2014, the curriculum used in the 2013 curriculum structured. Planning and conducting observation and conversation in Pamardi Siwi Kindergarten can be said to be good, because it is structured and systematic. This can be seen when the daily assessment is processed into weekly, monthly assessments, and so on for up to one semester.